Relationship-based Business Process Crowdsourcing? - O'Neill, Jacki; Martin, David (Springer, 2013)
New technologies do not always benefit the worker, especially when harnessed by organisations seeking ever cheaper labour. Crowdsourcing is a technology-enabled way of working which offers the potential to bring work to far flung communities. However, it is something of a double-edged sword and there are many socio-technical and ethical challenges. In the micro-task market crowdsourcing platforms tend to be designed largely for the advantage of the organisation requesting work, rather than the worker. This paper contributes to research calling to redress this balance [2, 6]. It describes the findings of anethnographic study of an outsourced business process – healthcare form digitization – as performed by workers in-office (India) and @Home (USA). It reveals the complexities of the relationships between worker and organisation and argues that designing some aspects of these relationships into crowdsourcing platforms and applications is as beneficial for the organisation as it is for the worker.